2005
DOI: 10.1111/j.1460-9592.2005.01426.x
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia for pediatric renal transplantation with and without epidural analgesia – a review of 7 years experience

Abstract: Anesthesia for renal transplantation in pediatric patients at CHW is safe and effective using a selected range of drugs and techniques. Pretransplant medical optimization, careful preoperative assessment, adequate monitoring and precise fluid management together with appropriate postoperative analgesia typify the perioperative care of CHW renal transplant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 32 publications
1
29
0
1
Order By: Relevance
“…Pediatric kidney transplant recipients receive large volumes of intravenous fluid in order to establish and maintain allograft perfusion . In addition to intraoperative crystalloid volumes approaching 200 mL/kg bodyweight, large volumes can be administered postoperatively to replace urine losses related to acute tubular injury.…”
Section: Introductionmentioning
confidence: 99%
“…Pediatric kidney transplant recipients receive large volumes of intravenous fluid in order to establish and maintain allograft perfusion . In addition to intraoperative crystalloid volumes approaching 200 mL/kg bodyweight, large volumes can be administered postoperatively to replace urine losses related to acute tubular injury.…”
Section: Introductionmentioning
confidence: 99%
“…The postoperative complication rate was significantly lower in the epidural group (5.5% vs. 20%, p<0.001) [19]. Postoperative epidural analgesia also improved the postoperative course following pediatric renal transplantation [20]. Among adolescents scheduled for scoliosis repair, a recent meta-analysis of all available studies (1966–2008) revealed that the administration of epidural local anesthetics plus intravenous opioids vs. intravenous opioids only was clearly associated with beneficial effects [21].…”
Section: Discussionmentioning
confidence: 99%
“…In 20 patients, patient controlled intravenous analgesia also had to be supplemented with systemic administration of opioids when the quality of the analgesia was inadequate [35]. There have been only a few studies so far on the potential risk of complications in patients who have undergone transplantation with PDA.…”
Section: Immunosuppression Following Organ Transplantationmentioning
confidence: 99%